2011
DOI: 10.1510/icvts.2011.275362
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative carriage and postoperative same-species sternal wound infection after cardiac surgery

Abstract: Sternal wound infection (SWI) after cardiac surgery remains an important problem. Prediction of pathogens involved in such infection could guide antibiotics. From April 1, 2006 to December 31, 2008, retrospectively, we evaluated the diagnostic value of preoperative methicillin-sensible Staphylococcus aureus (MSSA), methicillin-resistant S. aureus (MRSA) or multi-drug resistant Gram-negative bacillus (MDRGNB) carriage to predict same-pathogens involved in postoperative SWI. All patients referred for elective ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…In addition, there were no differences in mediastinitis or even SSIs. In agreement with our finding, Maillet and colleagues 11 suggested that MRSA colonization was a poor predictor of sternal wound infection. Of 128 patients who had SSIs, only 4 were MRSA carriers.…”
Section: Commentsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, there were no differences in mediastinitis or even SSIs. In agreement with our finding, Maillet and colleagues 11 suggested that MRSA colonization was a poor predictor of sternal wound infection. Of 128 patients who had SSIs, only 4 were MRSA carriers.…”
Section: Commentsupporting
confidence: 93%
“…10 Current single-center studies are limited by low MRSA prevalence, or, conversely, they overestimate MRSA carriage where it is endemic. 4,7,11 A broad-picture view of MRSA carrier prevalence nationwide in cardiac surgery and the outcomes in these patients is needed.…”
mentioning
confidence: 99%
“…In addition, when a preoperative infection causes low immunity at admission, colonized pathogen carriers more frequently develop multiantibiotic-resistant infections, a finding that is in agreement with previous reports. 38…”
Section: Discussionmentioning
confidence: 99%
“… 25 Testing the pre-operative prediction of pathogens, which may be involved in airway infection, could guide antibiotics. 26 Of course, the emergence of antimicrobial resistance has been contemporaneous with the intensive use of antibiotics. 27 Therefore, pre-operative antimicrobial therapy is not routinely recommended in all patients with high risks, but only in heavy smokers and patients of advanced age.…”
Section: Discussionmentioning
confidence: 99%